A Glimpse of China-African Union Economic Relations during 21st Century - Muhammad Amjad Raza; Dr. Abdul Basit Khan (Journal of Development and Social Sciences, 2024)
The ever-prospering China-African Union (AU) economic relations are the outcome of their long-term interaction. The dawn of 21st century marked a significant boost in this relationship with the establishment of the Forum on China-Africa Cooperation (FOCAC) and the New Partnership for Africa’s Development (NEPAD). Chinese Presidents Hu Jin Tao (2003-2013) and President Xi Jinping (2013- ) preferred to follow a multilateral approach towards African continent and interacted with AU through inter-regional organizations which policy radically transformed the level of Chinese penetration into the continent. The Agenda 2063 of AU has also been designed to maximize the benefits from China’s Belt & Road Initiative (BRI) of 2013. As a consequence of integrated efforts from China and the AU for the economic development of the continent, the collective economy of Africa had reached at a magnificent amount of $3 trillion in 2023. In this scenario, the current study, while reviewing policy documents and available literature, explores the nature of China's enhanced cooperation with Africa through regional and multilateral organizations such as the AU, FOCAC and NEPAD. It elucidates how China and AU had committed and cooperated in pursuit of the mantra 'build an even stronger community with a shared future'. Applying an explanatory and descriptive approach, the study concludes that China's extensive engagement with the AU to promote infrastructure development and connectivity has profoundly impacted African economic growth. Finally, it goes without saying that the analytics, assessments and outcomes of the study would help future researchers, academia and experts working on China’s economic engagements with the AU to rationally understand the impact of these relations.
Keywords: Agenda 2063; Belt and Road Initiative; China-African Union Economic Relations; FOCAC; NEPAD